(untitled) (Journal of the College of Basic Education, 2022)
To identify the happiness management of educational counselors from the General Directorates of Education in Baghdad affiliated to the Ministry of Education, and to achieve the goal of the research, the happiness management scale was built based on the realistic theory of William Blacher, which consists of (22) items. (200) by (80) men and (120) counselors, and then processing the data statistically using the statistical program (SPSS), as two types of honesty were extracted, they are from the discrimination of the paragraphs: 1- Apparent honesty by presenting the scale to experts and specialists. 2- The validity of the construction in the light of calculating the correlation of the paragraph with the degree of the scale. The researcher reached to extract the stability by two methods, the re-test method and the Cronbach method. The stability coefficient of the happiness management scale reached (0.84) and the reliability coefficient was (0.86) by the Alpha Cronbach method. From the results, the research concluded that the research sample has a high level of management Gentlemen in his duties Which recommendations are you?? The researcher pays attention to the educational counselor in the educational process and directs the media to the importance of psychological counseling.